PENGARUH PEMANFAATAN TEKNOLOGI INFORMASI, PERILAKU KINESIK DAN ARTEFAKTUAL, KOMPENSASI, DAN KEPERCAYAAN TERHADAP KEPUASAN PEMUSTAKA PERPUSTAKAAN NASIONAL RI - Adin Bondar (Ikatan Pustakawan Indonesia, 2015)
The purpose of this research is to determine the influence of the use of information technology, kinesics and artefactual behavior, compensation, trust towards customers sati4action. The research approach is quantitati e method with path analysis. Sampling technique is simple random sampling with a representative sample of 123 respondents.The result such as: first, the use of information technology, kinesics and artifactual behavior, compensatior, and trust has direct positive effect on customers satisfaction; second, the use of information technology, kinesics and artefactual behavior, and compensation, has direct positive effect on trust The implications of this research is to strengthen policies and role model in the improvement of libmry services as a vehicle for encouraging lifelor g education of reading habit society.